Enhancing Corrosion Resistance of AISI 1045 Carbon Steel Using Rosmarinus officinalis Extract: An Environmentally Friendly Approach - Pawawoi, Pawawoi; Putra, Adi Ganda; Lesmana, Dera; Prajitno, Djoko Hadi; Septianissa, Selly (Jurnal Kartika Kimia, 2025)
Corrosion is the greatest challenge faced by various industries, especially those in maritime regions. This study evaluates the effectiveness of Rosmarinus officinalis extract as a corrosion inhibitor for carbon steel AISI 1045 in artificial seawater. Steel samples with varying inhibitor concentrations (0, 30, 60, 90, and 120 ppm) were immersed for 25 days. The results indicate that the weight gain due to corrosion for the sample without an inhibitor reached 79.5 mg, while the use of rosemary significantly reduced the weight gain, with the lowest corrosion rates recorded at 90 ppm (0.003 mpy) and 120 ppm (0.005 mpy). The optimal inhibitor efficiency was achieved at 60 ppm (75.57%). Microstructural analysis showed a decrease in pitting corrosion thickness and the formation of a new phase, Fe₃O₄, which is more stable and protective. These findings emphasize the potential of rosemary extract as an environmentally friendly solution for controlling corrosion in carbon steel, particularly in corrosive environments like seawater.